Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijgi9100576
|View full text |Cite
|
Sign up to set email alerts
|

Improved Estimations of Nitrate and Sediment Concentrations Based on SWAT Simulations and Annual Updated Land Cover Products from a Deep Learning Classification Algorithm

Abstract: The agricultural sector and natural resources are heavily interdependent, comprising a coherent but complex system. The soil and water assessment tool (SWAT) is widely used in assessing these interdependencies for regional watershed management. However, long-term simulations of agricultural watersheds are considered as not realistic since they have often been performed assuming constant land use over time and are based on the coarse resolution of the existing global or national data. This work presents the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…To the south of the study area there is a Lignite mine, where the Public Power Company of Greece is undergoing intensive mining activity. More information about the area can be also found in [34,35]. The area is characterized by heterogeneous terrain which is the reason for the high variability in the soil properties in terms of the carbonate and organic matter contents, which range from a very high carbonate content in the northeast to very high organic matter content in the southwest (Figure 2).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…To the south of the study area there is a Lignite mine, where the Public Power Company of Greece is undergoing intensive mining activity. More information about the area can be also found in [34,35]. The area is characterized by heterogeneous terrain which is the reason for the high variability in the soil properties in terms of the carbonate and organic matter contents, which range from a very high carbonate content in the northeast to very high organic matter content in the southwest (Figure 2).…”
Section: Study Areamentioning
confidence: 99%
“…To the south of the study area there is a Lignite mine, where the Public Power Company of Greece is undergoing intensive mining activity. More information about the area can be also found in [34,35].…”
Section: Study Areamentioning
confidence: 99%
“…Additionally, soil erosion models, such as the Universal Soil Loss Equation (USLE) or the Revised Universal Soil Loss Equation (RUSLE) [48], simulate soil erosion processes and help identify areas prone to erosion, facilitating erosion control and soil conservation efforts. Moreover, hydrological models, such as the Soil and Water Assessment Tool (SWAT) [49], simulate water movement, infiltration, and runoff in landscapes, aiding in water resource management [50] and flood prediction. These advanced tools and simulations play a critical role in assessing the impacts of climate change, land management practices, and policy interventions on soil health, carbon dynamics, water resources, and overall ecosystem sustainability.…”
Section: High Precision Sensors Real Time Mappingmentioning
confidence: 99%
“…Since 2017, it has been demonstrated that deep learning (DL) networks (Shen, 2018; Shen et al., 2018), like long short‐term memory (LSTM; Hochreiter & Schmidhuber, 1997), can learn to predict environmental variables including stream temperature with exceptionally high accuracy (Rahmani, Lawson, et al., 2021; Rahmani, Shen, et al., 2021; Rehana & Rajesh, 2023; Sadler et al., 2022; Weierbach et al., 2022; S. Zhu & Piotrowski, 2020; Zwart et al., 2023). LSTM has shown its strength and versatility in simulating hydrologic variables such as soil moisture (Fang et al., 2017, 2019; J. Liu et al., 2022; O & Orth, 2021), streamflow (Feng et al., 2020, 2021; Khoshkalam et al., 2023; Xiang et al., 2020), dissolved oxygen (Heddam et al., 2022; Zhi et al., 2023), snow water equivalent (Broxton et al., 2019; Meyal et al., 2020), stream nitrate concentration (Saha et al., 2023; Samarinas et al., 2020), and radiation (Y. Liu et al., 2020; F. Zhu et al., 2021). However, mostly used as a forward simulator in hydrology, LSTM is also limited by its black‐box nature: it does not provide an interpretable explanation of internal processes, and its intermediate variables lack physical meaning and thus cannot be compared against observations to diagnose the model's internal logic (Appling et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu & Piotrowski, 2020;Zwart et al, 2023). LSTM has shown its strength and versatility in simulating hydrologic variables such as soil moisture (Fang et al, , 2019O & Orth, 2021), streamflow (Feng et al, 2020(Feng et al, , 2021Khoshkalam et al, 2023;Xiang et al, 2020), dissolved oxygen (Heddam et al, 2022;Zhi et al, 2023), snow water equivalent (Broxton et al, 2019;Meyal et al, 2020), stream nitrate concentration (Saha et al, 2023;Samarinas et al, 2020), and radiation (Y. Liu et al, 2020;F.…”
mentioning
confidence: 99%